Airway MMP-12 and DNA methylation in COPD: an integrative approach - Jonas Eriksson Ström; Simon Kebede Merid; Robert Linder; Jamshid Pourazar; Anne Lindberg; Erik Melén; Annelie F. Behndig (Respiratory Research)
Abstract Background In COPD, the balance between matrix metalloproteinases (MMPs) and their natural inhibitors [tissue inhibitors of metalloproteinases (TIMPs)] is shifted towards excessive degradation, reflected in bronchoalveolar lavage (BAL) as increased MMP concentrations. Because of their critical role in lung homeostasis, MMP activity is tightly regulated, but to what extent this regulation occurs through epigenetic mechanisms remains unknown. Methods To explore the interplay between MMPs, TIMPs, and DNA methylation (DNAm) we (1) analysed MMP-9, -12, and TIMP-1 concentrations in BAL fluid, and profiled DNAm in BAL cells from 18 COPD and 30 control subjects, (2) estimated protein–COPD relationships using multivariable regression, (3) identified protein quantitative trait methylation loci (pQTMs) with COPD as a potential modifier in a separate interaction model, and (4) integrated significant interactions with a previous COPD GWAS meta-analysis. Results COPD was associated with higher levels of BAL MMP-12 (p = 0.016) but not with MMP-9 or TIMP-1. Further examination of MMP-12 identified association with DNAm at 34 loci (pQTMs), with TGFBR2 (p = 2.25 × 10–10) and THBS4 (p = 1.11 × 10–9) among the top ten pQTM genes. The interaction model identified 66 sites where the DNAm–MMP-12 association was significantly different in COPD compared to controls. Of these, one was colocalized with SNPs previously associated with COPD. Conclusions Our findings indicate that airway MMP-12 may partially be regulated by epigenetic mechanisms and that this regulation is disrupted in COPD. Furthermore, integration with COPD GWAS data suggests that this dysregulation is influenced by a combination of environmental factors, disease processes, and genetics, with the latter potentially playing a lesser role.